An Institutional Rights Retention Strategy - Brekke, Camilla; Aspaas, Per Pippin (Open Science Talk, 2022)
Prorector for research and development at UiT The Arctic University of Norway informs about the institution's new Open Access Policy, in which Rights Retention takes a prominent place. All authors employed by UiT retain the rights to their peer-reviewed manuscripts, which can now be uploaded and be made available without any embargo period in the institutional repository, Munin, regardless of the policies of the publisher. In case an individual author refuses, (s)he is free to opt out, but no publisher shall have the right to force her/him to not make a manuscript publicly available in green open access through the institution's open repository. The original Norwegian policy document ("Prinsipper og retningslinjer for åpen tilgang til vitenskapelige publikasjoner ved UiT") is available through the website uit.no/publisering; an English translation will follow soon at en.uit.no/publishing. First published online: January 12, 2021